2014
DOI: 10.1016/j.dnarep.2014.02.020
|View full text |Cite
|
Sign up to set email alerts
|

DNA-PK: A dynamic enzyme in a versatile DSB repair pathway

Abstract: DNA double stranded breaks (DSBs) are the most cytoxic DNA lesion as the inability to properly repair them can lead to genomic instability and tumorigenesis. The prominent DSB repair pathway in humans is non-homologous end-joining (NHEJ). In the simplest sense, NHEJ mediates the direct re-ligation of the broken DNA molecule. However, NHEJ is a complex and versatile process that can repair DSBs with a variety of damages and ends via the utilization of a significant number of proteins. In this review we will des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
313
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(320 citation statements)
references
References 148 publications
(174 reference statements)
3
313
0
4
Order By: Relevance
“…As a third example, DNA-dependent protein kinase, which is well established to play a central role in the nonhomologous end joining pathway of DNA repair (66), is also reported to interact with DNA in the cytoplasm and to be essential for the full induction of innate immune responses to DNA and DNA viruses in fibroblasts (61,67,68). Ferguson et al found that the DNA-dependent protein kinase subunit Ku70 is in a complex with STING in resting cells, but this interaction is abrogated following DNA stimulation (61).…”
Section: Interactions Between the Cgas-cgamp-sting Pathway And Othermentioning
confidence: 99%
“…As a third example, DNA-dependent protein kinase, which is well established to play a central role in the nonhomologous end joining pathway of DNA repair (66), is also reported to interact with DNA in the cytoplasm and to be essential for the full induction of innate immune responses to DNA and DNA viruses in fibroblasts (61,67,68). Ferguson et al found that the DNA-dependent protein kinase subunit Ku70 is in a complex with STING in resting cells, but this interaction is abrogated following DNA stimulation (61).…”
Section: Interactions Between the Cgas-cgamp-sting Pathway And Othermentioning
confidence: 99%
“…Previous NHEJ models suggested that after binding of Ku to DNA ends, DNA-PKcs binds Ku:DNA to form a DNA-PK holoenzyme and bridges the broken ends (15)(16)(17)(18); however, recent experiments indicate that DNAPKcs may have different roles in NHEJ, such as the stabilization of core NHEJ factors, recruitment and retention of accessory factors, involvement in the DDR signaling cascade, and repair of complex and clustered DSBs (19)(20)(21)(22)(23)(24)(25). In addition, recent structural studies have shown that XRCC4 and XLF form filamentous structures in vitro (26)(27)(28).…”
mentioning
confidence: 99%
“…DNA-PK has a versatile role in NHEJ by forming complexes with other proteins and by its kinase activity (8,9). However, the importance of the catalytic subunit of this protein kinase, DNA-PKcs, during the NHEJ-dependent process of CSR has been uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other than DNA-PKcs selfphosphorylation, the functional relevance of its kinase activity is not fully understood (4,8). Furthermore, other kinases, such as ATM, have the ability to phosphorylate many of these proteins (9).…”
mentioning
confidence: 99%